Impact of Built Area on Increasing Surface Temperatures in Makassar City - Nasrul Nasrul; Medar M Nur; Nurfatimah Nurfatimah; Melda Vera; Isna Sulistia Ningsih; Tri Nur Alwiyah; Zakiyudaulah Muhammad; Rosmini Maru (Indonesian Journal of Fundamental and Applied Geography, 2025)
Makassar City, the fourth largest city in Indonesia and the main hub in Eastern Indonesia, covering an area of 175.8 km², has undergone significant changes due to the rapid rate of land conversion. This process has led to a decline in densely vegetated areas, which has impacted the rise in air temperature in built-up areas. This study aims to analyze the impact of built-up areas on the increase in air temperature in Makassar City. The data used were derived from MODIS imagery to measure air temperature changes, and analyzed using spatial analysis methods based on a spatial approach utilizing geographical data related to location. The results of the study indicate that air temperature levels in Makassar City in 2023 tended to be very high, although some areas were classified as having high and low-temperature levels. Based on these findings, strategic measures are recommended to control the rate of surface temperature increase, particularly through the development of green areas and the protection of water bodies as part of urban planning efforts.